Grain yield and food security evaluation in the yellow river basin under climate change and water resources constraints - Niu, Chen; Qi, Yafei; Guo, Aijun; Chang, Jianxia (Frontiers in Water, 2022)
With climate change, the amount of global water resources is decreasing and crop growth patterns are changing. Global food security will face severe challenges in future. Hence, it is of great significance to study the change in grain production under climate change and the water resources constraint to ensure national and regional food security. In this study, a complex system coupled with the hydrological model, crop model, and optimal regulation model of water resources has been constructed to explore the changes in future grain yield in the Yellow River Basin (YRB) under climate change and the water resources constraint, and further evaluate the future food security of the basin. The models show good adaptability. The results show that the precipitation and temperature in the YRB will be higher than the historical level and show an upward trend in future. On the contrary, runoff and irrigation water demand in the basin are lower than historical levels. Although the grain yield would decrease in future, the food security of YRB would be well-guaranteed. However, the level of food security in different provinces would be quite different. And some provinces will face serious food security problems without grain trade. This study will help relevant institutions in the YRB to deal with possible food security problems in future, and can also provide a reference for other countries and institutions in the world.